Towards zero burning peatland preparation: Incentive scheme and stakeholders role - MURNIATI MURNIATI; SRI SUHARTI (Society for Indonesian Biodiversity, 2018)
Murniati, Suharti S. 2018. Towards zero burning peatland preparation: Incentive scheme and stakeholders role. Biodiversitas 19: 1396-1405. Zero burning during peatland preparation should be implemented to prevent disturbance of its natural biodiversity as well as to minimize the triggering factors of forest fire incidents in Indonesia. The objective of the research is to study method and cost of peatland preparation, alternative incentive schemes to be applied in order to facilitate zero burning farming as well as to identify potential stakeholders involved in the implementation of the incentive. The research was done in Siak District, Riau Province during May to December 2016 through field observation and interview. Two groups of respondents interviewed in the research, i.e., peatland farmers (40 respondents) and officials of related institutions (32 respondents), who were selected through purposive sampling method. The results showed there were three methods of peatland preparation at the research sites practiced by the farmers: (i) Under control burning, (ii) Zero burning, manually and (iii) Zero burning, mechanically. Actual cost of zero burning is significantly higher or more than two times than that of under control burning method. Therefore, there is a need to provide the smallholders peatland farmers with an incentive scheme to support zero burning practice. Margin of cost between zero burning (manually) and under control burning of peatland preparation methods is recommended to be used as standard for incentive. The incentive should be in the form of compulsory programs and applied gradually to assure zero burning peatland preparation widely implemented. Potential stakeholders involved and their commitment to implement the incentive scheme should be encouraged.